Vitrectomy in Diabetic Retinopathy - Varun Gogia; Sumeet Khanduja; Shikha Gupta; Ashish Kakkar; Saptorishi Majumdar; S P Garg; Rajpal Vohra (Delhi Journal of Ophthalmology)
Diabetic retinopathy is an emerging cause of blindness throughout world. Despite adequate metabolic control and timely pan retinal photocoagulation some patients reach the stage of advanced diabetic retinopathy requiring surgical intervention. The surgical outcomes after diabetic vitrectomy have also steadily improved with advances in vitreoretinal surgical instrumentation. In this review authors have described the established indications, surgical techniques and recent advances in the management of diabetic retinopathy